Towards an optimal composition of general practitioners and nurse practitioners in out-of-hours primary care teams: a quasi-experimental study - Biezen, Mieke van der; Wensing, Michel (BMJ open, 2017)
Objectives To gain insights into the ability of general practitioners (GPs) and nurse practitioners (NPs) to meet patient demands in out-of-hours primary care by comparing the outcomes of teams with different ratios of practitioners. Design  Quasi-experimental study. Setting  A GP cooperative (GPC) in the Netherlands. Intervention  Team 2 (1 NP, 3 GPs) and team 3 (2 NPs, 2 GPs) were compared with team 1 (4 GPs). Each team covered 35 weekend days. Participants  All 9503 patients who were scheduled for a consultation at the GPC through a nurse triage system. Outcome measures  The primary outcome was the total number of consultations per provider for weekend cover between 10:00 and 18:00 hours. Secondary outcomes concerned the numbers of patients outside the NPs’ scope of practice, patient safety, resource use, direct healthcare costs and GPs’ performance. Results  The mean number of consultations per shift was lower in teams with NPs (team 1: 93.9, team 3: 87.1; p<0.001). The mean proportion of patients outside NPs’ scope of practice per hour was 9.0% (SD 6.7), and the highest value in any hour was 40%. The proportion of patients who did not receive treatment within the targeted time period was higher in teams with NPs (team 2, 5.2%; team 3, 8.3%) compared with GPs only (team 1 3.5%) (p<0.01). Team 3 referred more patients to the emergency department (14.7%) compared with team 1 (12.0%; p=0.028). In teams with NPs, GPs more often treated urgent patients (team 1: 13.2%, team 2: 16.3%, team 3: 21.4%; p<0.01) and patients with digestive complaints (team 1: 11.1%, team 2: 11.8%, team 3: 16.7%; p<0.01). Conclusions  Primary healthcare teams with a ratio of up to two GPs and two NPs provided sufficient capacity to provide care to all patients during weekend cover. Areas of concern are the number of consultations, delay in patient care and referrals to the emergency department. Trial registration NCT02407847
First published May 30, 2017
Gesehen am 06.07.2018